Why donors of foreign aid do not coordinate: The role of competition for export markets and political support - Andreas Fuchs; Peter Nunnenkamp; Hannes Öhler (Kiel Institute for the World Economy (IfW), 2013)
Development assistance has been criticized for a lack of coordination between aid donors. This paper argues that competition for export markets and political support prevents donor countries from closer coordination of aid activities. To test these hypotheses, we perform logit and fractional logit estimations for a large sample of recipient countries and aid activities since the early 1970s. Our empirical results reveal that export competition between donors is a major impediment to aid coordination. Tough less conclusive, we also find some evidence that donors' competition over political support prevents them from coordinating aid activities more closely.
Keywords: F35; F42; F53; 330; development aid; donor coordination; trade interests; export similarity; UN voting